Pengaruh Home Pharmacy Care terhadap Kepuasan Pelayanan Kefarmasian pada Pasien Hipertensi di Apotek Alula Farma Losari - Nopita, Juwita; Zuniarto, Ahmad Azrul; Nuari, Ris Ayu (An-Najat, 2025)
High-quality pharmaceutical services play a vital role in improving patient satisfaction, particularly among individuals with chronic conditions such as hypertension. One innovative approach to pharmaceutical care is Home Pharmacy Care (HPC), a service delivered directly to the patient’s home focusing on medication monitoring, patient education, and improving treatment adherence. This study aims to examine the effect of HPC on the satisfaction of pharmaceutical services among hypertensive patients at Alula Farma Pharmacy, Losari. The research employed a pre-experimental design with a pre-test and post-test without a control group. A total of 30 hypertensive patients were selected using non-probability purposive sampling. The research instrument used was a validated and reliable pharmaceutical service satisfaction questionnaire, which covered several dimensions, including responsiveness, empathy, assurance, reliability, and tangibility. Data analysis was conducted using the Wilcoxon signed-rank test. The results showed that HPC had a significant positive effect on patient satisfaction, with a significance value of 0.001 (p < 0.05). The most notable improvements were observed in the aspects of responsiveness, empathy, and reliability, reflecting better patient–pharmacist interaction and trust in service delivery. These findings indicate that HPC is an effective strategy to enhance patients’ perceptions of pharmaceutical service quality. Furthermore, the implementation of HPC highlights the potential to reduce barriers to accessing care, promote better medication adherence, and strengthen patient-centered services. It is expected that this study can serve as a foundation for the development and broader application of home-based pharmaceutical care models, particularly in the management of chronic diseases.